PENDAMPINGAN PENGELOLAAN LAPORAN ZAKAT FITRAH MENGGUNAKAN APLIKASI EXCEL PADA MASJID AL-IKHLAS - Santoso, Setiyo Hadi; Aisyah, Nur (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
This community service has the aim of providing assistance in managing zakat fitrah reports at the Amil Zakat Infak and Shodaqoh Institution (LAZIS) using the Excel Application where previously data management was still using manual methods, assistance in using excel is useful to facilitate the management of the Amil Zakat Infak and Shodaqoh Institution (LAZIS) at the Al-Ikhlas Mosque. The method used in this assistance uses a qualitative descriptive approach, namely by using interviews, lectures, and direct training on the management of the Amil Zakat Infak and Shodaqoh Institution (LAZIS) using the excel application. After the assistance was held in the management of the Amil Zakat Infak and Shodaqoh Institution (LAZIS), the mosque administrators had knowledge and could operate excel in managing the data of the Amil Zakat Infak and Shodaqoh Institution (LAZIS) at the Al-Ikhlas Mosque, Joyo Grand Housing Rw 09, Merjosari Village, Lowokwaru Subdistrict, Malang so that the data was more accurate and data management was more efficient.